PENGARUH KEPRIBADIAN INTROVERT DAN EXTROVERT TERHADAP KINERJA KARYAWAN UD FAUDHO BERSAUDARA - Zein Hunaifie, Fauzan; Yusuf , Tamzil; Adam Avicena Moorcy, Muhammad (MEDIA RISET EKONOMI [MR.EKO], 2025)
This study aims to determine the influence of Introvert and Extrovert personalities on Employee Performance at UD Faudho Bersaudara. The population used in this study was 30 people from May 2025 - June 2025. The sample used in this study was 30 respondents, the research method used a quantitative method with a saturated sample technique. Data collection was carried out by observation, documentation, and distribution of questionnaires. This study uses SPSS (Statistical Package For The Social Sciences) in managing data. The results of the analysis in partial testing with (t-test) and (f-test) where the introvert and extrovert personality variables have a positive effect on improving performance.